REAKSI SAHAM INDEKS LQ45 TERHADAP PENGUMUMAN KABINET KERJA TAHUN 2014 DI BURSA EFEK INDONESIA - Muhamad Soleh; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2014)
This research entitle LQ45 stock reaction to the announcement of the cabinet work in 2014 on thestock exchange Indonesia. This analysis technique applies traditional techniques saturated samples. The population of 45 companies in LQ45 period of August 2014-January 2015 with the observation period of 10 days before and 10 days after the announcement/ the analaytical approach used to determine the stock price reaction before and after using one sample t test, while an analysis approach to distinguish the average of abnormal return and trading volume by using a paired sample t test using the alpha level () of 5%. The results of collecting data is to analyze of stock price reaction. It shows that there is no stock price reaction before and after the announcement of the Working cabinet. Because of abnormal return only occurs on H-7 (0.024) and H+8 (0.018), while others do not. The researches used a writting test. Test results of the test on average abnormal return is no difference in the average abnormal return and the announcement of the cabinet work before and after. The test results mean that there are many differences in volume average trading volume before and after the announcement of Labor cabinet.